Automation of a reactor for enzymatic hydrolysis of sugar cane bagasse : Computational intelligencebased adaptive control - Furlong, Vitor Badiale (2015)
The continuous demand growth for liquid fuels, alongside with the decrease of fossil oil reserves, unavoidable in the long term, induces investigations for new energy sources. A possible alternative is the use of bioethanol, produced by renewable resources such as sugarcane bagasse. Two thirds of the cultivated sugarcane biomass are sugarcane bagasse and leaves, not fermentable when the current, first-generation (1G) process is used. A great interest has been given to techniques capable of utilizing the carbohydrates from this material. Among them, production of second generation (2G) ethanol is a possible alternative. 2G ethanol requires two additional operations: a pretreatment and a hydrolysis stage. Regarding the hydrolysis, the dominant technical solution has been based on the use of enzymatic complexes to hydrolyze the lignocellulosic substrate. To ensure the feasibility of the process, a high final concentration of glucose after the enzymatic hydrolysis is desirable. To achieve this objective, a high solid consistency in the reactor is necessary. However, a high load of solids generates a series of operational difficulties within the reactor. This is a crucial bottleneck of the 2G process. A possible solution is using a fed-batch process, with feeding profiles of enzymes and substrate that enhance in the process yield and productivity. The main objective of this work was to implement and test a system to infer online concentrations of fermentable carbohydrates in the reactive system, and to optimize the feeding strategy of substrate and/or enzymatic complex, according to a model-based control strategy. Batch and fed-batch experiments were conducted in order to test the adherence of four simplified kinetic models. The model with best adherence to the experimental data (a modified Michaelis-Mentem model with inhibition by the product) was used to train an Artificial Neural Network (ANN) as a softsensor to predict glucose concentrations. Further, this ANN may be used in a closedloop control strategy. A feeding profile optimizer was implemented, based on the optimal control approach. The ANN was capable of inferring the product concentration from the available data with good adherence (Determination Coefficient of 0.972). The optimization algorithm generated profiles that increased a process performance index while maintaining operational levels within the reactor, reaching glucose concentrations close to those utilized in current first generation technology a (ranging between 156.0 g.L⁻¹ and 168.3 g.L⁻¹). However rough estimates for scaling up the reactor to industrial dimensions indicate that this conventional reactor design must be replaced by a two-stage reactor, to minimize the volume of liquid to be stirred.